1995
DOI: 10.1093/clinids/20.4.790
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Acquisition of Multiresistant Acinetobacter baumannii: Risk Factors and Prognosis

Abstract: To identify risk factors for and prognostic indicators of the nosocomial acquisition of multiresistant Acinetobacter baumannii in an intensive care unit, we prospectively studied 40 patients: 13 who were infected with this organism and 27 who were colonized. Isolates were identified by pulsed-field gel electrophoresis; the infected/colonized patients were compared with 348 noninfected, noncolonized patients by logistic regression analysis and with matched historical controls in a cohort study. The severity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
1
11

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(128 citation statements)
references
References 31 publications
1
115
1
11
Order By: Relevance
“…[3] Recent studies have had mixed results to indicate mortality attributable of Acinetobacter. Some authors reported increased mortality rates secondary to Acinetobacter [19] while others including ours found not. [20] A. baumannii isolates common with relatively higher MDR rates may be due to habits of frequent prescribing or using wide spectrum antimicrobials in our country.…”
Section: Discussionmentioning
confidence: 49%
“…[3] Recent studies have had mixed results to indicate mortality attributable of Acinetobacter. Some authors reported increased mortality rates secondary to Acinetobacter [19] while others including ours found not. [20] A. baumannii isolates common with relatively higher MDR rates may be due to habits of frequent prescribing or using wide spectrum antimicrobials in our country.…”
Section: Discussionmentioning
confidence: 49%
“…have emerged as important pathogens of ICUs, most of them being resistant to ampicillin, carbenicillin, cefotaxime, chloramphenicol, and gentamicin. 7,8 In our study, Acinetobacter spp was the number one cause of pneumonia based on samples gathered from the tracheal aspirate and shows resistance to ceftriaxone (85.1%), ceftazidime (88.8%), amikacin (86.2%), gentamicin (84.4%) and fluoroquinolones (86.2-89.2%) respectively. This is consistent with the results of a similar study conducted in India.…”
Section: Discussionmentioning
confidence: 68%
“…Acinetobacter baumannii is the species most often responsible for a wide spectrum of nosocomial infections [68,113,136]. It is infections such as bloodstream infections, ventilator-associated pneumonia, urinary tract infections and wound infections [113,124,129,136].…”
Section: Introduction -Acinetobacter Baumanniimentioning
confidence: 99%